Lyrics - Sting, (Musician) (New York : Dial Press, 2007)
Presents the lyrics of songs written by Sting which appeared on twelve albums issued between 1978 and 2003, and includes comments from Sting on the albums and many of the individual songs.
Includes indexes.
Adult
Keywords: Sting, -- (Musician); Sting, -- (Musician); Songs -- Texts; Songs -- Texts